Perfil e prática do agente de segurança socioeducativa: recomendações para a subsecretaria de atendimento às medidas socioeducativas de Minas Gerais - Bauer, Marcela (2013)
This study discusses and identifies aspects that influence the profile and practice of the socioeducational security agent (ASSE) by means of his relationship with the guidelines of the socioeducational assistance policy. For this, the ASSE is regarded as a key actor in the process for implementing this policy. Through a comparative study between the reality observed in the states of Minas Gerais and Rio Grande do Sul, supported on in-depth interviews with 22 actors (principals and agents), observation of the structure and dynamics of 6 inpatient units, and documentary survey of the institutional strategies involved in the practice of this policy. We identified that the multiplicity of assignments required in the professional practice of ASSEs is far from being achieved in the reality of the units, and it is more feasible to focus on the collective profile or the socioeducational security team profile. Based on the interviews and analyses conducted, we designed recommendations for improvement with regard to three aspects: institutional change, material change, and dissemination and transformation of values.